An axial turbine in an innovative oscillating water column (OWC) device for sea-wave energy conversion. (15th September 2018) - Hashem, I.; Abdel Hameed, H.S.; Mohamed, M.H.
Abstract: Wells turbines, self-rectifying air-driven axial turbines, are typically used to convert pneumatic power available in the periodic reversed airflow in Oscillating Water Column (OWC) device into mechanical energy. However, such turbines suffer from low aerodynamic efficiency; low powers produced, and narrow operating range. The current work proposes the operating principle of using water as the working fluid rather than air by submerging the Wells turbine in the sea water to enhance its performance. This gives an advantage for the turbine operation with a fluid having specific weight higher fluid than air. The analysis is carried out for an innovative device proposed by Boccotti in which a vertical axis hydraulic Wells turbine installed inside a vertical duct and contained in a caisson below the sea water surface. The CFD simulations are performed depend on the steady 3D incompressible Reynolds Averaged Navier-Stokes (RANS) calculations on this type of axial turbine rotor with realizable k − ε turbulence model. A comparative analysis between the computational results and experimental results is carried out and a good agreement is found between both results. This paper proved that, the hydraulic (immersed) Wells turbine performance is better than that of the air (conventional) Wells turbine. A substantial improvement in the torque coefficient is achieved with the hydraulic turbine of about 1.4 times the torque of the conventional air turbine. Using water as a working fluid which is the proposed concept leads to a wider operating range unlike using air. In addition, the effects of blade profile and rotor solidity on the turbine performance were clarified computationally. In this work, two kinds of symmetric blade profiles have been used (NACA 0015 and S1046). The present computational investigation was carried out for three rotor solidities (0.64, 0.48 and 0.24) through changing the number of turbine blades (8, 6 and 3 blades). It is found that for a hydraulic Wells turbine operating under oscillating water flow, the rotor geometry preferred is the blade profile of S1046 for the investigated three values of rotor solidities. Highlights: The Present study considers a new concept to convert wave energy. Investigation is performed depend on the steady 3D Reynolds Averaged Navier-Stokes. Water-driven Wells turbine performance is better than the one which driven by air. Wells turbine is tested with different airfoils under water and air working fluids. Using the water driven concept will lead to wider operating range unlike using air.